2012
DOI: 10.1258/jrsm.2012.110330
|View full text |Cite
|
Sign up to set email alerts
|

Proposed MHRA changes to UK children's paracetamol dosing recommendations: modelling study

Abstract: SUMMARYObjectives Paracetamol is the most commonly administered medicine to children. A recent study highlighted the risk of overdose of paracetamol using British National Formulary for Children (BNFC) age-based dosing guidelines. This current study assesses the safety of changes to the UK paracetamol product dosing system proposed by the Medicines and Healthcare products Regulatory Authority (MHRA) which include a larger number of narrower age bands and a single dose per age band.Design Theoretical comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In addition, a recent UK study found that, even when administered under current instructions, underweight children are at risk of receiving approximately twice, and average weight children up to 133% of, the recommended single and cumulative daily dose of paracetamol; this has led to recently proposed changes in dosing recommendations (Eyers et al 2012a , b ). Two reports of hepatotoxicity in association with dosages reported to be in the therapeutic range (Heubi et al 1998 ; Makin et al 1995 ) may represent inaccurate memory of the administered doses or a narrower paracetamol therapeutic window because of associated conditions.…”
Section: Specific Safety Issuesmentioning
confidence: 99%
“…In addition, a recent UK study found that, even when administered under current instructions, underweight children are at risk of receiving approximately twice, and average weight children up to 133% of, the recommended single and cumulative daily dose of paracetamol; this has led to recently proposed changes in dosing recommendations (Eyers et al 2012a , b ). Two reports of hepatotoxicity in association with dosages reported to be in the therapeutic range (Heubi et al 1998 ; Makin et al 1995 ) may represent inaccurate memory of the administered doses or a narrower paracetamol therapeutic window because of associated conditions.…”
Section: Specific Safety Issuesmentioning
confidence: 99%
“…Thereafter, the oral paracetamol was continued 6 hourly for 72 hours. [ 8 ] The researcher contacted the parents/caregivers 6 hours after discharged from hospital via mobile phone to know the pain scores and time the first dose of analgesia was administered to the patients at home. The parents/caregivers were duly informed to record the pain scores in the FLACC score sheet and they brought the FLACC score sheet to the outpatient clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Current UK dosing guidelines are age-based (Table 4 ). However, a recent UK study found that underweight children are at risk of receiving approximately 200 %, and average-weight children up to 133 % of the recommended single and cumulative daily dose of paracetamol, leading to recently proposed changes in dosing recommendations [ 71 , 72 ]. To reduce the risk of overdosing or underdosing, dosing guidelines in some other countries are based on weight or both age and weight; the typical recommendation for ibuprofen is 5–10 mg/kg per dose, while for paracetamol it is 10–15 mg/kg per dose [ 1 , 22 , 73 ].…”
Section: Treating the Distressed Feverish Childmentioning
confidence: 99%